Design for children's apps - Costa Ferrer, Maria (UPV[Scientia], 2017)
Are children under 2 years old exposed to apps? Which ones? How often? What kind of apps would be best suited for small children based on their physical and cognitive development, the evolution of their play patterns and their ability to interact with mobile devices? How to design apps as appropriate as possible for children under 2 years old? These are some of the main questions that are answered through the research presented in this publication. An investigation that demonstrates that children under 2 years of age in Spain are playing with apps and highlights the relevance of generating supporting documentation, for improving the use and the design of apps for such a vulnerable target. The research presents pioneering information for the industry and developers with specific proposals on how to design children's apps taking into consideration children's development and their possibilities in terms of recreational, educational, graphical and interactive content. The information also supports educators and parents when it comes to choosing apps and defining the ways of use that may be most appropriate for each child in each age group.